IMPACT OF ADJUVANT FAT GRAFTING ON IMPROVED UPTAKE AND HEALING OF SPLIT THICKNESS SKIN GRAFT AT TERTIARY CARE HOSPITAL - Anwar, Saira; Faisal Akhlaq Ali khan; Waqas Sami; Maryam Noor; Rabeeaa Farrukh; Sindhu Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Since the 1980s, autologous fat grafting has been one of the most widely used methods in plastic surgery to treat volume and contour problems. There are many advantages of autologous fat, i.e., it is cheap, biocompatible, and readily available autologous tissue in large quantities, minimal morbidity. Objective was to compare the outcomes of fat grafting combined with STSGs and STSGs alone in patients with chronic non-healing wounds presenting at a tertiary care hospital. Methods: It was a prospective cohort study carried out at the Department of plastic surgery, Civil hospital Karachi, Pakistan from 11th April to 12th October 2023. Patients aged 18-60 years with chronic non-healing wounds due to burn, trauma, or infection lasting at least six weeks were included. Group A received fat grafting followed by STSGs, while Group B received STSGs alone. Follow-up for both groups continued for 4-5 weeks, focusing on graft uptake and healing, with successful graft take defined as wound healing upon clinical examination. Data was analyzed by SPSS version 25. Results: Overall, the mean age of the patients was 36.47±8.57 years. In Group A, the median width was 8.00 cm, and in Group B, it was 7.00 cm, this difference was statistically significant (p=0.005). The proportion of healing in group A was significantly higher as compared to group B (66.7% vs 30%, (p=0.001). The odds of wound healing were 0.21 times lower in group B as compared to group A (95% CI=0.07 to 0.63). After adjusting for duration and width of wound, the odds of wound healing in group B remains significantly lower as compared to odds of wound healing in group A (OR=0.13, 95% CI=0.03 to 0.54). Conclusion: The combination of fat grafting with split-thickness skin grafts holds promising result for improved wound healing in patients with chronic non-healing wounds.